Implementation of goods and services tax in the construction industry - Siti Noorshaiza Ishak, 1972- , author 610843 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Sarjana Sains (Pengurusan Kontrak Pembinaan))